Antiretroviral Therapy Adherence as a Relational Process: The Roles of U=U Awareness, Discrimination, and Viral Suppression among People Living with HIV in Steady Partnerships in Indonesia - Dwi Kartika Rukmi; Rizqi Wahyu Hidayati; Kharisma Kharisma; Fika Lilik Indrawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
ntroduction: Adherence to antiretroviral therapy (ART) is a central determinant of treatment success among people living with HIV (PLWH). However, how relational and psychosocial factors operate within steady partnerships to shape adherence remains insufficiently understood in the Indonesian context. This study aimed to examine key predictors of ART adherence among PLWH in steady partnerships, focusing on individual, relational, and therapy-related factors in Yogyakarta, Indonesia. Methods: A cross-sectional survey was conducted among 370 PLWH with steady partners across five districts in Yogyakarta between April and July 2025 using a self-administered questionnaire. Descriptive statistics, bivariate analyses, and binary logistic regression were applied to identify factors independently associated with ART adherence. Results: Overall, 78.4% of respondents demonstrated good ART adherence. In the adjusted logistic regression model, understanding the Undetectable = Untransmittable (U=U) concept (AOR = 2.26; 95% CI: 1.02–4.98; p = 0.043), absence of HIV-related discrimination (AOR = 0.46; 95% CI: 0.26–0.82; p = 0.008), and having an undetectable viral load (AOR = 2.64; 95% CI: 1.61–4.32; p < 0.001) emerged as the strongest independent predictors of adherence. Other relational variables, including partner support and ART duration, were associated with adherence in bivariate analyses but did not remain significant after adjustment. Conclusions: These findings indicate that ART adherence among PLWH in steady partnerships is primarily shaped by treatment-related knowledge, stigma-free social environments, and virological outcomes. HIV care programs should prioritize U=U–based education, stigma reduction strategies, and routine viral load monitoring to sustain adherence. Relational and partner-based approaches may hold programmatic relevance but warrant further investigation through longitudinal or intervention-based studies to clarify their independent contribution to ART adherence in Indonesia.